Forest Stand Structure and Pattern of Old-Growth Western Hemlock/Douglas-Fir and Mixed-Conifer Forests - Malcolm North; Jiquan Chen; Brian Oakley; Bo Song; Mark Rudnicki; Andrew Gray; Jim Innes (Forest Science, 2004)
With fire suppression, many western forests are expected to have fewer gaps and higher stem density of shade-tolerant species as light competition becomes a more significant influence on stand pattern and composition. We compared species composition, structure, spatial pattern, and environmental factors such as light and soil moisture between two old-growth forests: Pacific Northwest western hemlock/Douglas-fir at the Wind River Canopy Crane Research Facility exhibiting gap-phase replacement and southern Sierra Nevada mixed conifer at the Teakettle Experimental Forest after 135 years without a fire. We hypothesized that fire suppression at Teakettle would create a current tree composition and distribution more like Wind River where light is an important influence on stand dynamics. Wind River has nearly continuous canopy cover and a high foliage volume that severely reduces understory light and stratifies the canopy composition by shade tolerance. Large trees are regularly spaced from 0 to 15 m and shade-tolerant and intolerant species are “repelled.” In contrast, Teakettle's canopy cover is discontinuous, foliage volume is one-fifth that of Wind River, and understory light is 15 times higher. Trees at Teakettle are significantly clustered in groups containing a mix of shade-tolerant and -intolerant species, separated by large gaps. Although Teakettle's gaps have higher moisture and a thinner litter layer than tree groups, regeneration in gaps is scarce. Fire suppression has increased stem density at Teakettle but it has not filled in gaps, stratified the canopy by shade tolerance, or produced a composition consistent with patterns at Wind River. Teakettle's distinctly clustered stem distribution may result from a minimum canopy cover threshold needed for tree establishment. If high temperatures produced by direct sunlight inhibit stem patterns, traditional stand management that reduces canopy cover to release regeneration should be applied with caution in the southern Sierra Nevada. FOR. SCI. 50(3):299–311.